SURGICAL MANAGEMENT OF POSTPARTUM AND PELVIC HAEMORRHAGE - Riaz, G Sarwar; Saeed, Fauzia (Journal of Ayub Medical College Abbottabad, 1992)
Despite the ready availability of banked blood and blood products, postpartum and pelvic haemorrhage remains one of the major causes of mortality and morbidity all over the world. In developing countries, as in Pakistan, it is among the first three causes of maternal mortality. Sixty-one cases were included in this study over a period of nine years from various hospitals, such as 1. Maternity and Children Hospital, Dammam (Saudi Arabia) Affiliated with King Faisal University Al-Khobar (Saudi Arabia). 2. Services Hospital, Lahore. Affiliated with Allama Iqbal Medical College, Lahore (Pakistan). 3. Bahawal Victoria Hospital, Bahawalpur. Affiliated with Quaid-e-Azam Medical College, Bahawalpur (Pakistan). Our management mainly based on surgical treatment alongwith conventional therapy. KEY WORDS: 1. Postpartum and Pelvic Haemorrhage. 2. Hypogastric Artery Ligation (HAL)